2000
DOI: 10.1063/1.873826
|View full text |Cite
|
Sign up to set email alerts
|

Inboard/outboard asymmetry of poloidal flow observed in the Compact Helical System

Abstract: The poloidal flow velocity and the density of fully ionized carbon were measured in the Compact Helical System ͓K. Ida et al., Phys. Rev. Lett. 67, 58 ͑1991͔͒ using the charge exchange spectroscopy with the bidirectional viewing. The poloidal asymmetry of the poloidal flow velocity observed in the outward shifted plasma is due to the electrostatic potential being constant on the magnetic flux surfaces. The poloidal asymmetry of the ion density can be explained by the conservation of the poloidal ion flux under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…Recently, from various edge plasma measurements in ETB plasmas in the CHS, it is suggested that the edge pedestal region, where the ion pressure gradients and a corresponding ion flow are expected, is very narrow (for e.g., ∆r/a ≈ 0.05) if it exists [6]. Radial profiles of the flow velocities and the ion temperatures in such a narrow region could not be detected with the previous CXS geometry at a vertically elongated section [11] with the chord spacing ∆R = 7.5 mm in a major radial direction corresponding to a spatial resolution of ∆r/a ≈ 0.06. Even though a vertical view at horizontally elongated sections subtends a limited radial range, it has superior spatial resolution near the edge region.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Recently, from various edge plasma measurements in ETB plasmas in the CHS, it is suggested that the edge pedestal region, where the ion pressure gradients and a corresponding ion flow are expected, is very narrow (for e.g., ∆r/a ≈ 0.05) if it exists [6]. Radial profiles of the flow velocities and the ion temperatures in such a narrow region could not be detected with the previous CXS geometry at a vertically elongated section [11] with the chord spacing ∆R = 7.5 mm in a major radial direction corresponding to a spatial resolution of ∆r/a ≈ 0.06. Even though a vertical view at horizontally elongated sections subtends a limited radial range, it has superior spatial resolution near the edge region.…”
Section: Introductionmentioning
confidence: 97%
“…Especially in studies of radial electric fields, note that we do not measure directly the dominant ion component of the plasmas. We can know not only the flow velocity and the temperature of the impurity ion, but also the impurity density profile from the intensity of the charge exchange excited lines [11]. In the study of the transition phenomenon in the ETB plasmas, however, we must consider the density profile of the proton and thus the impurity density profile is out of scope of this paper.…”
Section: Charge Exchange Spectroscopic Measurementmentioning
confidence: 99%
See 3 more Smart Citations